Magnetic fluctuations driven insulator-to-metal transition in Ca(Ir(1−x)Ru(x))O(3) - Gunasekera, J. (Sci Rep, 2015)
Magnetic fluctuations in transition metal oxides are a subject of intensive research because of the key role they are expected to play in the transition from the Mott insulator to the unconventional metallic phase of these materials, and also as drivers of superconductivity. Despite much effort, a clear link between magnetic fluctuations and the insulator-to-metal transition has not yet been established. Here we report the discovery of a compelling link between magnetic fluctuations and the insulator-to-metal transition in Ca(Ir(1−x)Ru(x))O(3) perovskites as a function of the substitution coefficient x. We show that when the material turns from insulator to metal, at a critical value of x ~ 0.3, magnetic fluctuations tend to change their character from antiferromagnetic, a Mott insulator phase, to ferromagnetic, an itinerant electron state with Hund’s orbital coupling. These results are expected to have wide-ranging implications for our understanding of the unconventional properties of strongly correlated electrons systems.